An evaluation of public initiatives to change behaviours that affect water quality - Gianluca Grilli; John A. Curtis (The Economic and Social Research Institute (ESRI), 2021)
Pollution and environmental depletion are often caused by human behaviours, where if behaviours were modified, environmental pressure could be substantially reduced. Many public programmes aim to influence people to change their unsustainable behaviours but few undertake ex-post evaluations of behavioural change programmes. This paper undertakes an evaluation of a 5-year programme to understand whether community engagement activities lead to more sustainable practices. Using a treatment and control experiment, the research investigates whether programme participants are representative of the wider population, whether participation leads to sustainable practices, whether pro-environmental behaviours are sustained over time and the relative effectiveness of different types of events on individual behaviours. Overall, results suggest that water engagement event participants are more likely to adopt sustainable behaviours, however, attendees only represent a small cohort of the wider population, which possibly hinders a wider adoption of good practices. With respect to individual behaviours, different outcomes were detected for different behaviours, which suggests that not all behaviours were equally amenable to change. When comparing the impact of different events, events that are focused on building community ties were more successful than events with simple provision of information. Finally, new pro-environmental behaviours tend to be abandoned after a period of time, therefore re-engagement at regular time intervals is advised.
Keywords: 330